Analisis Strategi Bersaing KSPPS Zam-Zam Barokah Menggunakan Competitive Profile Matrix (CPM) di Kecamatan Cilongok - Ita Solihatun; Bahar Habibi; Humamul Hakim; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study discusses business development strategies at KSPPS Zam-Zam Barokah, located in the Cilongok District. As a Sharia-based financial institution, this KSPPS operates without using an interest-based system. In facing competition with conventional financial institutions, KSPPS Zam-Zam Barokah is required to implement innovative and responsive strategies. In addition, the Competitive Profile Matrix (CPM) method is used to highlight the strengths and weaknesses of competitors. The KSPPS offers various savings products such as Qurban, Pension, Mudharabah, and Wadiah, as well as financing products including Murabahah, Musyarakah, Ijarah, and Qardh, all of which comply with Sharia principles. The findings emphasize the importance of strengthening human resources, developing technology, expanding cooperation networks, and diversifying business efforts to ensure sustainability and enhance the competitiveness of the KSPPS amidst the current economic developments